Pengaruh Kualitas Sistem, Kualitas Informasi dan Kualitas Layanan Terhadap Kepuasan Pengguna SILALAPBAJA - Rosinta Setiaji Fracini; Yohanes Suhari (Elkom : Jurnal Elektronika dan Komputer, 2024)
The study titled "The Influence of System and Service Quality on User Satisfaction of Silalapbaja Website" aims to evaluate the impact of each independent variable on the dependent variable. There were 51 respondents involved in this research, with data analysis conducted using SPSS version 25. The results indicate that System and Service Quality significantly influence User Satisfaction, as evidenced by the significant value of Fhitung = 0.000 < 0.05. From the t-test, System and Service Quality variables partially affect User Satisfaction, while Information Quality does not have a significant partial effect. For instance, the significant values of thitung X1 = 0.000 < 0.05 and X3 = 0.49 < 0.05, whereas X2 = 0.094 > 0.05. The variables that significantly influence are System Quality with a Standardized Coefficients Beta of 0.552 and Service Quality of 0.220. Based on the research findings, it can be concluded that System, Information, and Service Quality contribute to 59% of User Satisfaction, while other factors beyond this study affect 41%. Therefore, it is recommended for the developers of the Silalapbaja Website to prioritize improvements in System and Service Quality to enhance User Satisfaction.